Hormonal crosstalk controls cell death induced by kinetin in roots of Vicia faba ssp. minor seedlings - Kaźmierczak, Andrzej; Tarkowská, Danuše; Plačková, Lenka; Doniak, Magdalena; Doležal, Karel (Scientific reports, 2023)
Studies of vitality/mortality of cortex cells, as well as of the concentrations of ethylene (ETH), gibberellins (GAs), indolic compounds/auxins (ICs/AUXs) and cytokinins (CKs), were undertaken to explain the hormonal background of kinetin (Kin)-regulated cell death (RCD), which is induced in the cortex of the apical parts of roots of faba bean (Vicia faba ssp. minor) seedlings. Quantification was carried out with fluorescence microscopy, ETH sensors, spectrophotometry and ultrahigh-performance liquid chromatography tandem mass spectrometry (UHPLC‒MS/MS). The results indicated that Kin was metabolized to the transport form, i.e., kinetin-9-glucoside (Kin9G) and kinetin riboside (KinR). KinR was then converted to cis-zeatin (cZ) in apical parts of roots with meristems, to cis-zeatin riboside (cZR) in apical parts of roots without meristems and finally to cis-zeatin riboside 5'-monophosphate (cZR5'MP), which is indicated to be a ligand of cytokinin-dependent receptors inducing CD. The process may be enhanced by an increase in the amount of dihydrozeatin riboside (DHZR) as a byproduct of the pathway of zeatin metabolism. It seems that crosstalk of ETH, ICs/AUXs, GAs and CKs with the cZR5'MP, the cis-zeatin-dependent pathway, but not the trans-zeatin-dependent pathway, is responsible for Kin-RCD, indicating that the process is very specific and offers a useful model for studies of CD hallmarks in plants.
Keywords: kyseliny indoloctové; Cytokinins; tandemová hmotnostní spektrometrie; zeatin; buněčná smrt; Indoleacetic Acids; Tandem Mass Spectrometry; Cell Death; Zeatin; kinetin; Seedlings; Vicia faba; semenáček; Kinetin; cytokininy